Bioactive waste-derived glass ionomer cements with enhanced mechanical and antibacterial properties - Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Ahmad Khiri, Mohammad Zulhasif; Cheong, Wei Mun; Foong, Phey Yee (Elsevier, 2025)
The development of sustainable dental materials has become increasingly important due to growing environmental concerns and demand for bioactive restoratives. In this study, waste-derived glass ionomer cements (GICs) were synthesized using soda lime silica (SLS) glass and clam shells (CS) as sources of SiO2 and CaO, respectively. Three different GIC formulations (GIC1.0, GIC1.2, and GIC1.4) with varying water content were prepared and evaluated based on their mechanical properties, antibacterial activity against Streptococcus mutans , and fluoride ion release over an ageing period of 28 days. Among the tested compositions, GIC1.2 exhibited the highest compressive strength (119.14 ± 11.57 MPa) and Vickers microhardness (191.33 ± 19.51 HV) after 28 days. Antibacterial tests using the Kirby-Bauer disk diffusion method revealed an inhibition zone of 22.00 mm in pellet form and 26.00 mm in the aged solution form, highlighting the efficacy of long-term fluoride ion diffusion. Ion chromatography confirmed a progressive increase in fluoride release, reaching 194.82 ppm at 28 days. These findings demonstrate the viability of converting glass and shell waste into high-performance GICs suitable for dental restorative applications, offering both mechanical durability and sustained bioactivity.